The poplar Phi class glutathione transferase: expression, activity and structure of GSTF1 - Pégeot, Henri; Koh, Cha San; Petre, Benjamin; Mathiot, Sandrine; Duplessis, Sébastien; Hecker, Arnaud; Didierjean, Claude; Rouhier, Nicolas (Frontiers in Plant Science, 2014)
Glutathione transferases (GSTs) constitute a superfamily of enzymes with essential roles in cellular detoxification and secondary metabolism in plants as in other organisms. Several plant GSTs, including those of the Phi class (GSTFs), require a conserved catalytic serine residue to perform glutathione (GSH)-conjugation reactions. Genomic analyses revealed that terrestrial plants have around 10 GSTFs, 8 in the Populus trichocarpa genome, but their physiological functions and substrates are mostly unknown. Transcript expression analyses showed a predominant expression of all genes both in reproductive (female flowers, fruits, floral buds) and vegetative organs (leaves, petioles). Here, we show that the recombinant poplar GSTF1 (PttGSTF1) possesses peroxidase activity towards cumene hydroperoxide and GSH-conjugation activity towards model substrates such as 2,4-dinitrochlorobenzene, benzyl and phenetyl isothiocyanate, 4-nitrophenyl butyrate and 4-hydroxy-2-nonenal but interestingly not on previously identified GSTF-class substrates. In accordance to analytical gel filtration data, crystal structure of PttGSTF1 showed a canonical dimeric organization with bound GSH or MES molecules. The structure of these protein-substrate complexes allowed delineating the residues contributing to both the G and H sites that form the active site cavity. In sum, the presence of GSTF1 transcripts and proteins in most poplar organs especially those rich in secondary metabolites such as flowers and fruits, together with its GSH-conjugation activity and its documented stress-responsive expression suggest that its function is associated with the catalytic transformation of metabolites and/or peroxide removal rather than with ligandin properties as previously reported for other GSTFs.